2020
DOI: 10.1111/joa.13206
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the female pelvic nerves: a macroscopic study of the hypogastric plexus and their relations and variations

Abstract: The autonomic nerves of the lesser pelvis are particularly prone to iatrogenic lesions due to their exposed position during manifold surgical interventions. Nevertheless, the cause of rectal and urinary incontinence or sexual dysfunctions, for example after rectal cancer resection or hysterectomy, remains largely understudied, particularly with regard to the female pelvic autonomic plexuses. This study focused on the macroscopic description of the superior hypogastric plexus, hypogastric nerves, inferior hypog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…Urogenital dysfunction is principally related to injury of the nerve fibers of PANS, which is usually irreversible (19), and great attention needs to be paid to the preservation of the HGN, PSN, and PP due to their variation. Aurore et al (20) revealed that an accessory HGN could be found in 25% of samples, with two main patterns observed. In 56% of samples thick robust nerve bundles were found, while in 44% a rough meshwork of fibers intermingling with blood vessels was seen.…”
Section: Discussionmentioning
confidence: 99%
“…Urogenital dysfunction is principally related to injury of the nerve fibers of PANS, which is usually irreversible (19), and great attention needs to be paid to the preservation of the HGN, PSN, and PP due to their variation. Aurore et al (20) revealed that an accessory HGN could be found in 25% of samples, with two main patterns observed. In 56% of samples thick robust nerve bundles were found, while in 44% a rough meshwork of fibers intermingling with blood vessels was seen.…”
Section: Discussionmentioning
confidence: 99%
“…The plexus has either the aspect of a nerve fiber network or that of a compact lamina of nervous tissue [ 5 ]. The branches are relatively well-organized around the blood vessels that supply the pelvic viscera.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the paracervix and USL contain the pelvic splanchnic nerves, the distal part of the hypogastric nerve, and the IHP ( Figure 7 ). The IHP is composed of sympathetic fibers from the hypogastric nerve and parasympathetic fibers from the splanchnic nerves and nerve anastomoses (which arise from the second-to-fourth sacral roots) [ 27 ]. Efferent fibers from the IHP travel to the rectum, uterus, rectovaginal ligament, and deep vesicouterine ligament.…”
Section: Anatomical Considerations and Surgical Implicationsmentioning
confidence: 99%